2007
DOI: 10.1007/s10565-007-0185-6
|View full text |Cite
|
Sign up to set email alerts
|

Thapsigargin, a selective inhibitor of sarco-endoplasmic reticulum Ca2+-ATPases, modulates nitric oxide production and cell death of primary rat hepatocytes in culture

Abstract: Increased cytosolic calcium ([Ca2+]i) and nitric oxide (NO) are suggested to be associated with apoptosis that is a main feature of many liver diseases and is characterized by biochemical and morphological features. We sought to investigate the events of increase in [Ca2+]i and endoplasmic reticulum (ER) calcium depletion by thapsigargin (TG), a selective inhibitor of sarco-ER-Ca2+ -ATPases, in relation to NO production and apoptotic and necrotic markers of cell death in primary rat hepatocyte culture. Culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 69 publications
1
12
1
1
Order By: Relevance
“…[3][4][5][6]. Treatment of myotubes with thapsigargin (2 M) for 4 h to inhibit uptake of calcium by the sarcoplasmic reticulum also caused an increase in NFAT transcriptional activity, as previously reported (2). Similar to the calcium ionophore experiment, cotreatment with L-NAME inhibited this effect (Fig.…”
Section: L-name Inhibits Calcium-induced Nfat-dependent Transcriptionsupporting
confidence: 67%
See 1 more Smart Citation
“…[3][4][5][6]. Treatment of myotubes with thapsigargin (2 M) for 4 h to inhibit uptake of calcium by the sarcoplasmic reticulum also caused an increase in NFAT transcriptional activity, as previously reported (2). Similar to the calcium ionophore experiment, cotreatment with L-NAME inhibited this effect (Fig.…”
Section: L-name Inhibits Calcium-induced Nfat-dependent Transcriptionsupporting
confidence: 67%
“…N G -nitro-L-arginine methyl ester (L-NAME), 1H- [1,2,4]oxadiazolo [4,3-a]quinoxalin-1-one (ODQ), 3-(5Ј-hydroxymethyl-2Јfuryl)-1-benzyl indazole (YC-1), diethylenetriamine-NONO (DETA-NO), methylamine hexamethylene methylamine-NONO (MAHMA-NO), and 3-(2-hydroxy-2-nitroso-1-propylhydrazino)-1-propanamine-NONO (PAPA-NO) were obtained from Cayman Chemical (Ann Arbor, MI). Lithium chloride (LiCl) was purchased from Acros Organics (Morris Plains, NJ).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Increasing SERCA2b levels reduce ER stress in the liver and increases glucose tolerance [69]. The SERCA inhibitor thapsigargin induces an increase in cytosolic calcium content with a decrease in ER calcium resulting in mitochondrial cytochrome C release and apoptosis of cultured primary rat hepatocytes [70]. …”
Section: Molecular Mechanisms Related To Hepatic Steatosis In Nafldmentioning
confidence: 99%
“…In those articles, we looked for possible underlying common mechanisms of cytoprotection from molecular levels to whole animal studies of various structurally unrelated molecules. We found that several compounds experimentally showed some hepato-ameliorative properties and enumerated possible explanations (Canova et al, 2007;Cerny et al, 2009;Farghali & Masek, 1998;Farghali et al, 1991aFarghali et al, ,b, 1994Farghali et al, , 1996aFarghali et al, ,b, 1997Farghali et al, , 2000bFarghali et al, , 2002Farghali et al, , 2003Gasbarrini et al, 1992aGasbarrini et al, ,b, 1993Kmonickova et al, 2001;Lekic et al, 2011;Sakr et al, 1991a,b).…”
Section: Scientific Rationale For the Traditional Use Of Some Plants mentioning
confidence: 84%